Body Size Preferences and Food Choice Among Normal and Overweight Mothers and Children in Malawi (P10-070-19) - Flax, Valerie (Curr Dev Nutr, 2019)
OBJECTIVES: Overweight in mothers and children in sub-Saharan Africa is rapidly increasing and may be related to body size preferences. The objective of this study was to measure mothers’ preferences for their own and their child's body size and how they relate to food choices. METHODS: We enrolled 271 mothers and their children (6–59 months) in Lilongwe and Kasungu Districts. Based on standard body-mass index and weight-for-height z-score cutoffs, 78 mothers (29%) were normal weight and 193 (71%) were overweight; 120 children (44%) were normal weight and 151 (56%) were overweight. Interviewers used a set of 7 adult female and 7 child body silhouette drawings and a semi-structured question guide to measure mothers’ perceptions of their own and their child's preferred and healthy body sizes and how their preferences affected food choices. We performed chi-squared tests comparing body size perceptions and grouped open-ended responses by weight status. RESULTS: Mothers’ selection of silhouettes that represented their body size preferences (67% normal weight, 68% overweight preferred overweight) and perceptions of a healthy body size (96% normal weight, 94% overweight selected overweight as healthy) did not differ by their weight status. A higher percentage of mothers of overweight than normal weight children preferred overweight child body sizes (70% vs. 48%, P = 0.003). Mothers’ perceptions of a healthy child body size (89% normal weight, 94% overweight selected overweight as healthy) did not differ by the child's weight status. To attain a larger body size, mothers said they could eat or feed the child larger quantities or more frequently and increase consumption of fatty/oily foods and drinks (such as sodas, sweetened yoghurt, and milk), but many cannot afford to do this. CONCLUSIONS: Malawian mothers had strong preferences for overweight body sizes for themselves and mixed preferences for their children. Their desired strategies for increasing weight indicate that body size preferences may drive food choice but could be limited by cost. FUNDING SOURCES: Drivers of Food Choice (DFC) Competitive Grants Program, funded by the UK Government's Department for International Development and the Bill & Melinda Gates Foundation, and managed by the University of South Carolina, Arnold School of Public Health.